An Analysis of Interpersonal Meaning in Madurese Folktale “Mutiara Yang Tersisa” - Nur Ijabah; Kurrotu Ainy; Qadrina Lailyn Amrullah (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Interpersonal meaning has an important role in communication. Interpersonal meaning can express social role relationships between communication partners. This research examines the analysis of interpersonal meaning in the Madurese folktale “Mutiara Yang Tersisa”. The purpose of this research is to describe (1) how the interpersonal meaning is realized in this folktale and (2) to find out the dominant type of mood that characterizes the folktale. This research used a qualitative method with a descriptive approach. This research data was taken from the clauses in the folktale. The author collected data by observation and documentation. The findings showed that (1) the use of mood and modality is identified as a realization of interpersonal meaning that complements the linguistic characteristics of folktale with the narrative type of text and (2) the most dominant type of mood is the declarative mood which is used to express and share information to create engagement between writer and reader.